QANUN OF SHARIA FINANCIAL INSTITUTIONS: ECONOMIC BENEFITS AND MAQĀSID AL-SYARĪ'AH - Danial Danial (IAIN Lhokseumawe, 2023)
This study focuses on two things, namely; first, explaining the substance of Qanun Aceh Number 11 of 2018 and second, finding and explaining the connection of this Qanun with the economic benefits of the Acehnese community in the perspective of maqāsid al-syarīah. Through the literature study and data document review of the Aceh Statistics Agency, it was found: First, Qanun Aceh Number 11 of 2018 has been in effect in Aceh for 4 (four) years. This law consists of XII chapters and 67 articles. In consideration, the philosophical, historical, sociological, and juridical foundations of this qanun are explained. This study found that all financial institutions operating in Aceh must be based on sharia principles even if they are not labeled sharia. This conclusion is reinforced by the explanation of article 3 of this law in relation to the universal basis that adheres to the principled system of conducting business activities in the financial field that applies in general while still referring to sharia principles. This conclusion shows that this Qanun offers the Islamization of financial institutions in Aceh substantially not formally. Second, in the perspective of maqāsid al-syarī'ah, this Qanun has not shown a significant increase in the economic benefits of the people of Aceh. This conclusion is supported by BPS Aceh data on economic benefits. There are 4 (four) indicators used to measure it, namely; economic growth rate, CPI, poverty profile, and financial access to UMKM. The word has not been used to explain that this Qanun has only been implemented for 4 (four) years and was interrupted by the Covid 19 pandemic. Therefore, it cannot be concluded that the SFI Qanun does not affect the economic benefits of the Acehnese community. Unless it has not given a significant influence for the economic benefits of Aceh practically-factually.